COMPARATIVE STUDY OF SAFETY AND EFFICACY OF AZITHROMYCIN AND AMOXICILLIN IN TREATING CHILDREN WITH LOWER RESPIRATORY TRACT INFECTION - Balaji, Veluchamy; Sivaraj, R.; Nirmala, P. (International Journal of Current Pharmaceutical Research, 2015)
Objectives: Lower respiratory infections are common among school going children. Frequent infections are troublesome children and to their parents and may lead to respiratory complication such as Chronic Bronchitis, bronchiolitis and bronchial asthma. Frequent dropouts in schools and may affect the studies of the children. So there is a need of an effective and safe drug for the infection. Methods: The study was with 40 patients of the age group between 1 to 12 years, who were diagnosed with the lower respiratory infection. The patients were divided in to two groups. Group A Amoxicillin group (n=40) was treated Amoxicillin with 40 mg/day. Group B Amoxicillin group (n=40) was treated 10 mg/day. Both the drugs were orally. Clinical evaluation of symptoms was assessed before and after treatment (3rd and 7th days). Patient's White Blood cell Counts, Lymphocytes counts were analyzed accordingly. Results: At the end of the treatment (3rd and 7th days) the clinical evaluation, WBC and Lymphocytes count in Azithromycin group showed significant reduction of WBCs (12.1%) and Lymphocyte counts (8.2%) than amoxicillin group. Minimal adverse drug reactions were noted in Azithromycin group. Conclusion: There is clear evidence that Azithromycin is superior to amoxicillin in treating lower respiratory infections in children.